Image Enhancement By Using Homomorphic Filtering Model - Amel H.Abbas; Jamila Harbi S (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
A number of techniques have been proposed in the literature to deal with the illumination induced appearance variations ranging from simple image enhancement techniques, such as histogram equalization or gamma intensity correction. In this paper we proposed a homomorphic filtering model or the logarithmic total variation model to enhance non uniform illumination in real experimental image. This model will be enhancing the brightness in high frequency and in low frequency. We improved the image by using the output resulted from our proposed model as input again to this model, the final enhanced image is de-noised from all unwanted details and the edge will be enhanced in all direction. Some fidelity parameters is applied and we obtain an acceptable results.